The Routledge companion to English studies / edited by Constant Leung, Brian V. Street - Leung, Constant editor
English is now a global phenomenon no longer defined by fixed territorial, cultural and social functions. The Routledge Companion to English Studies provides an authoritative overview of the subject area. Taking into account the changing conceptualizations of English, this Companion considers both historical trajectories and contemporary perspectives while also showcasing the state-of-the-art contributions made by the established scholars of the field. -- Back cover.